2021
DOI: 10.33963/kp.15763
|View full text |Cite
|
Sign up to set email alerts
|

Two-­year prognosis of patients hospitalized for decompensated heart failure in a district general hospital

Abstract: Background Patients hospitalized for heart failure (HF) exacerbation tend to have a poor prognosis. Most previous studies were performed in large clinical centers and detailed analyses of patients with HF hospitalized in district general hospitals are lacking. aims The aim of this study was to assess the outcomes of patients admitted with HF exacerbation to a district general hospital. methods We retrospectively enrolled patients hospitalized for HF exacerbation in the years 2010 to 2011 (191 patients) and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…RV failure has been repeatedly shown to compromise the prognosis in heart failure. In a recent study, it was confirmed to be an independent prognostic factor of all-cause mortality and rehospitalization for heart failure [6]. It underlines the need for the search for therapies focused on preserving RV function in heart failure.…”
Section: Resultsmentioning
confidence: 89%
“…RV failure has been repeatedly shown to compromise the prognosis in heart failure. In a recent study, it was confirmed to be an independent prognostic factor of all-cause mortality and rehospitalization for heart failure [6]. It underlines the need for the search for therapies focused on preserving RV function in heart failure.…”
Section: Resultsmentioning
confidence: 89%
“…It should be noted that the percentage of patients enrolled in the study with implantable cardioverter-defibrillators (including cardiac resynchronization therapy) is disproportionately small concerning the number of patients with LVEF < 40 % and even lower in the elderly patients (Table 4). We precisely analyzed and discussed this problem in our previous study [15]. It also seems interesting that the subgroup with the composite end-points, was characterized by a higher rate of implanted ICD/CRT.…”
Section: Comparison Of Post-hospital Recommendations According To the Agementioning
confidence: 97%
“…This study is a sub-analysis of our retrospective project [15] of all patients hospitalized with a diagnosis of acutely decompensated chronic HF and new-onset acute HF [16] in at a single cardiology department (St. Vincent Hospital in Gdynia, Poland) during 2016-2017. Further analysis included: the patient's biometric parameters, the medical history available in the documentation (with particular emphasis on comorbidities, condition of the coronary vessels, implanted devices, the treatment so far), physical examination findings documented during hospitalization, laboratory results, electrocardiography and echocardiography [15]. The data was obtained from the hospital's medical records and electronic patient records.…”
Section: Patients Selectionmentioning
confidence: 99%
“…Despite continuous progress in both pharmacological therapy and invasive methods (McDonagh et al 2021) (McDonagh et al 2021; Ahmed et al 2021; Hussein et al 2019), all-cause mortality in HF patients remains high with substantial economic burden on healthcare systems (Spencer et al 2018; Savarese et al 2022). HF is the leading cause of hospitalizations, resulting in more than 1 million admissions in both the United States and Europe (Blecker et al 2013; Dobrowolska et al 2021).…”
Section: Introductionmentioning
confidence: 99%